Dysfunction of the Microbiota-Gut-Brain Axis in Neurodegenerative Disease: The Promise of Therapeutic Modulation With Prebiotics, Medicinal Herbs, Probiotics, and Synbiotics - Christine Tara Peterson PhD (SAGE Publishing, 2020)
Recent data suggest gut microbiota dysbiosis as a contributing factor in neurodegenerative diseases, such as Parkinson's Disease (PD) and Alzheimer's Disease (AD), and these pathologies may manifest via the microbiota-gut-brain-axis, which comprises bidirectional communication through neuroimmune, neuroendocrine, and direct neural pathways such as the vagus nerve. Preclinical and human clinical trial data reveal exciting potential for novel treatment targets and therapeutic modulation with prebiotics, medicinal herbs, probiotics, and synbiotics in health, aging, and neurodegeneration and are reviewed here. While greater insights and characterization of the microbiota-gut-brain axis have been revealed over the past decade, salient questions related to the pathology, pathogenesis and clinical treatment of the axis in the context of both health and neurodegenerative disease remain and are discussed in this review. Future directions such as additional well-controlled, large scale, longitudinal human clinical trials are urgently needed to further elucidate both mechanism and therapeutic opportunity in health, neurological disease, and disease subpopulations to ensure that the next decade ushers the dawn of targeted therapeutic modulation of the microbiota-gut-brain axis.